Thursday

April 24, 2014

April 24, 2014

Posted by **shae** on Monday, April 30, 2012 at 11:25pm.

- math -
**visoth**, Monday, April 30, 2012 at 11:31pmtimes everything in parenthesis by 8

giving you

2x - 8x - 8y = y - x combine like terms

-6x - 8y = y - x

add x to both side

-5x - 8y= y

-y from both side

-5x -9y=0

- math -
**visoth**, Monday, April 30, 2012 at 11:33pmand it depends on which variable you want but im sure you can figure it out from here

**Related Questions**

TO KIM - can you help me with this |2x - 3|^2 - 6|2x - 3| + 5=0 I know you are ...

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

math - Simplify sin^2x+cos^2x+sec^2x -tan^2x+csc^2x-cot^2x

math - if x is not equal to negative 3/2, (2x^3-x^2-6x)/(2x+3)equals? a. x-2 b. ...

math - translate and simplify"six less than twice the sum of a number and three...

math - Which equation demonstrates the commutative property of addition? a. 2x+y...

Math - Prove each identity: a) 1-cos^2x=tan^2xcos^2x b) cos^2x + 2sin^2x-1 = sin...

Math33333 - Please help me! Problem: x+2 x-3 _________ - _________ 2x^2+5x+2 2x^...

math - how many times does the graph of y= 2x squared -2x+3 intersect the x-axis...

Math - Can someone please check this for mistakes please? y=4(x+3)-2x y=4x+3-2x ...